New treatment techniques for axillary hyperhidrosis. (October 2014) - Mordon, Serge R.; Trelles, Mario A; Leclère, Franck Marie; Betrouni, Nacim
Abstract: Hyperhidrosis is a medical problem defined as perspiration in excess of what is normally needed to cool the body. The excessive production of sweat by the sudoriferous glands is independent of the process of thermoregulation. Techniques have recently appeared that make use of energy sources, in particular microwave devices and light (pulsed flashlamp or laser). The aim is to obtain very long-lasting efficacy without notable side effects. Thermal Nd:YAG lasers used with an interstitial fiber, microwave devices, and photodynamic therapy appear to offer new treatment options for axillary hyperhidrosis. However, insertion of a laser fiber into tissue by means of a cannula may lead to complications if the procedure is not well mastered, as has been shown by numerous studies on laser lipolysis. The only microwave device available on the market is certainly interesting. Photodynamic therapy using eosin gel is an attractive technique. The energy source is a pulsed flashlamp, which many physicians have. Eosin gel is relatively easy to produce and these gels are already marketed in several countries. However, further clinical studies of larger series of patients and with longer follow-up are still needed to reach a definitive conclusion as to the value of this approach.